Kinetic modeling of CO2 methanation over a Ni3Fe/Al2O3 catalyst. - Sanz Monreal, Pablo; Mercader Plou, Víctor; Durán Sánchez, Paúl; Francés Pérez, Eva; Herguido Huerta, Javier; Peña Llorente, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2024)
Several kinetic models of the Langmuir-Hinshelwood type have been considered for the experimental fitting to the methanation of CO2. Their coefficients have been determined using Non-Linear Regression and subsequently evaluated from a statistical and thermodynamic point of view.